Entrepreneurship Education as a Catalyst for Sustainability: Linking Innovation, Intention, and Business Models - Purwana, Dedi; Effendi, Mohammad Sofwan; Adha, Maulana Amirul; Musyaffi, Ayatulloh Michael; Suparno, Suparno (International Review of Management and Marketing, 2025)
Sustainable entrepreneurship has become an essential approach for tackling global issues associated with climate change, social injustice, and the degradation of the environment. This research intends to investigate the role of Entrepreneurship Education in influencing Sustainability Business Models through the mediating effects of Sustainability Innovation and Sustainability Intention. Using a quantitative approach, data were collected from 240 young entrepreneurs in Indonesia who have participated in sustainable entrepreneurship activities. SEM was utilized to analyze the relationships among the factors. The findings reveal that EE directly impacts SInn, SInt, and SBM. Furthermore, SInn significantly influences SInt and SBM, while SInt also positively affects SBM. Notably, EE indirectly impacts SBM through the mediators SInn and SInt, highlighting the importance of innovation and intention in translating entrepreneurial education into sustainable business practices. This research enhances the existing literature by integrating EE, SInn, SInt, and SBM into a comprehensive framework. It provides empirical evidence from a developing country context, offering insights into how education programs can foster sustainable entrepreneurship among young entrepreneurs. These findings underline the necessity of developing educational programs for entrepreneurs that prioritizes innovation and sustainability values.